Diagnostic Accuracy of Diffusion Weighted Magnetic Resonance Imaging for Detection of Prostate Cancer Keeping Histopathology as Gold Standard - MARYAM SAMAD; SARA NISAR; SAMIA ABBAS; MUDASSIR MALIK; KHAWAR SHAHZAD; MUHAMMAD HASEEB MALIK (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Prostate cancer is considered the most common tumour among males. In recent years, there has been a shift towards noninvasive techniques for diagnosing prostate cancer through diffusion weighted imaging (DWI). It can avoid unnecessary biopsy in many cases. Aim: To evaluate the diagnostic accuracy of DWI for prostate cancer diagnosis, keeping histopathology as the gold standard. Methods: This cross-sectional study was conducted in the radiology department of Bahawal Victoria Hospital, Bahawalpur, from May 2023 to October 2023. We conducted a cross-sectional study in the radiology department of BVH, Bahawalpur, from May 2023 to October 2023. Prior approval was taken from the institutional ethical review board. 55 patients were included with elevated PSA levels and symptoms suspicious for prostate cancer. The DWI imaging was evaluated for prostate cancer, and the final results were compared with histopathological diagnosis. Results: The mean age of patients was 59.85±5.60 years. The sensitivity, specificity, and diagnostic accuracy of DWI for prostate cancer diagnosis were 84.2%, 83.3%, and 83.6%, respectively. Conclusion: DWI is an alternative, noninvasive technique for the diagnosis of prostate cancer with high diagnostic accuracy. Keywords: histopathology, diffusion weighted imaging (DWI), prostate-specific antigen (PSA)